Asset price misalignments and the role of money and credit - Dieter Gerdesmeier; Hans-Eggert Reimers; Barbara Roffia (Verein für Socialpolitik, 2010)
This paper contributes to the literature on the properties of money and credit indicators for detecting asset price misalignments. After a review of the evidence in the literature on this issue, the paper discusses the approaches that can be considered to detect asset price busts. Considering a sample of 17 OECD industrialised countries and the euro area over the period 1969 Q1 - 2008 Q3, we construct an asset price composite indicator which incorporates developments in both the stock price and house price markets and propose a criterion to identify the periods characterised by asset price busts, which has been applied in the currency crisis literature. The empirical analysis is based on a pooled probit-type approach with several macroeconomic monetary, financial and real variables. According to statistical tests, credit aggregates (either in terms of annual changes or growth gap), changes in nominal long-term interest rates and investment-to-GDP ratio combined with either house prices or stock prices dynamics turn out to be the best indicators which help to forecast asset price busts up to 8 quarters ahead.
Keywords: E37; E44; G10; 330; Asset prices; house prices; stock prices; financial crisis; asset price busts; probit models; monetary aggregates; credit aggregates